A Case Study on Optimal Sizing of Battery Energy Storage to Solve 'Duck Curve' Issues in Malaysia - Wong L.A.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric load flow; Electric power transmission networks; Electric utilities; Renewable energy resources; Secondary batteries; Smart power grids; Solar power generation; Battery energy storage; Battery energy storages (BES); Independent system operators; Load profiles; Optimal sizing; Reverse Power flows; Solar photovoltaics; Voltage fluctuations; Battery storage